DEVELOPING COMPENSATORY COMPETENCE IN ENGLISH SPEAKING: A DIAGNOSTIC STUDY OF STUDENTS AND TEACHERS IN UZBEKISTAN (SCIENCE TIME JOURNAL, 2026)
This study investigates the use of compensatory strategies in English oral communication among undergraduate students and English language teachers. The aim was to assess the level of awareness and application of these strategies in real-life speaking situations. A diagnostic survey was administered to 94 students and 26 teachers from pedagogical and linguistic institutions. The results revealed that while teachers consistently employ a wide range of compensatory strategies such as paraphrasing, simplification, and clarification requests, students tend to use them less frequently and often lack conscious control over their communication process. The findings suggest a clear need to integrate compensatory strategy instruction into language education to enhance learners’ communicative competence and confidence. This research contributes to the growing body of studies advocating for strategic competence development as a core component of foreign language instruction.